IN VITRO ANTICANCER POTENTIAL OF BIOSYNTHESIZED ZINC OXIDE NANOPARTICLES FROM THE SEAWEED TURBINARIA CONOIDES - R, KHOUSHIKA RAAJSHREE; Durairaj, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to investigate the anticancer potential of zinc oxide nanoparticles (ZnO-NPs) and hydroethanolic extract of Turbinaria conoides (HETC) against Dalton's lymphoma ascites (DLA) cell line. Methods: Nanoparticles were synthesized from the HETC. An ultraviolet-visible spectrophotometric analysis was performed to confirm the formation of ZnO-NPs. Size, morphology, and elemental composition of ZnO-NPs were also analyzed using scanning electron microscope-energy dispersive X-ray diffraction. The cytotoxic activity of ZnO-NPs and HETC was evaluated by 3-(4,5-dimethythiazol-. 2-yl)-2,5-diphenyltetrazolium bromide (MTT) and trypan blue dye exclusion assays on DLA cells. The apoptosis inducing the effect was observed through acridine orange staining method (AO and EB) and DNA ladder assay. Results: The results of in vitro cytotoxic studies by MTT and trypan blue dye exclusion assays on DLA cell line in the presence of ZnO-NPs showed an IC50 value of 23.13 and 25.81 Î¼g/ml, respectively. The DNA ladder assay and AO/EB staining clearly demonstrated that the ZnO-NPs at 50 Î¼g/ml concentration induced a maximum apoptosis in DLA cells when compared with HETC. Conclusion: In the present study, the cytotoxic and apoptotic inducing effect of the synthesized ZnO-NPs and HETC were assessed, and it was found that ZnO-NPs possessed potent anticancer effect against DLA cells.